2021
DOI: 10.1177/0020731421994842
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impact of Individual Characteristics and Neighborhood Socioeconomic Status During the COVID-19 Pandemic in the Provinces of Milan and Lodi

Abstract: Social inequalities in health are known to be influenced by the socioeconomic status of the territory in which people live. In the context of the ongoing coronavirus disease 2019 (COVID-19) pandemic, this study is aimed at assessing the role of 5 area-level indicators in shaping the risk of contagion in the provinces of Milan and Lodi (Lombardy, Italy), namely: educational disadvantage, unemployment, housing crowding, mobility, and population density. The study area includes the municipalities at the origin of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
1
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 51 publications
4
46
1
2
Order By: Relevance
“…According to the Danish authorities, 15 residential areas are currently defined as social housing (SH) areas, characterized by low employment rates, low income, low education level, high crime rate and/or increased proportion of immigrants (3). Some reports suggest that ethnic minorities in a number of countries are over-represented among those infected with COVID-19, just as socioeconomic inequality is described among SARS-CoV-2 infected persons (4)(5)(6). A Danish report from October 2020 showed similar patterns, where people of non-Western background accounted for 25.7% of cases with SARS-CoV-2 infection, despite representing only 8.9% of the population (7,8).…”
Section: Introductionmentioning
confidence: 97%
“…According to the Danish authorities, 15 residential areas are currently defined as social housing (SH) areas, characterized by low employment rates, low income, low education level, high crime rate and/or increased proportion of immigrants (3). Some reports suggest that ethnic minorities in a number of countries are over-represented among those infected with COVID-19, just as socioeconomic inequality is described among SARS-CoV-2 infected persons (4)(5)(6). A Danish report from October 2020 showed similar patterns, where people of non-Western background accounted for 25.7% of cases with SARS-CoV-2 infection, despite representing only 8.9% of the population (7,8).…”
Section: Introductionmentioning
confidence: 97%
“…A current systematic review concluded that apart from the individual-level factors like age and sex, community-level factors such as socioeconomic status could affect the temperature-mortality association ( Son et al, 2019 ). Italy has seen significant socioeconomic inequalities such as educational disparity and unemployment in the context of the COVID-19 pandemic ( Consolazio et al, 2021 ), which played a crucial role in vulnerability to high and low temperatures ( Marí-Dell'Olmo et al, 2019 ). Our results show that a higher cold-related mortality risk during the 2020 COVID-19 pandemic than the same months during 2015–2019 but with no difference for the changes in the heat effects.…”
Section: Resultsmentioning
confidence: 99%
“…Inequality as regards the risk of contracting COVID-19 is due to the fact that certain individuals, communities, and populations are at a higher risk of contracting the infection or of contracting a particularly severe infection [ 4 ] than others. The first risk is linked to individual circumstances [ 5 ] (immunodepression), social circumstances [ 6 ] (community living, close living quarters, homelessness), and work-related circumstances [ 7 , 8 ] (frequent contact with the public, poor protection in the work environment) [ 9 ].…”
Section: Healthcare Inequality and The Covid-19 Pandemicmentioning
confidence: 99%